2018
DOI: 10.1523/jneurosci.0540-18.2018
|View full text |Cite
|
Sign up to set email alerts
|

Coherent Activity between the Prelimbic and Auditory Cortex in the Slow-Gamma Band Underlies Fear Discrimination

Abstract: The medial prefrontal cortex and the basolateral amygdala (BLA) are essential for discriminating between harmful and safe stimuli. The primary auditory cortex (Te1) sends projections to both sites, but whether and how it interacts with these areas during fear discrimination are poorly understood. Here we show that in male rats that can differentiate between a new tone and a threatening one, the selective optogenetic inhibition of Te1 axon terminals into the prelimbic (PL) cortex shifted discrimination to fear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 47 publications
1
24
0
Order By: Relevance
“…Our finding of fear discrimination in males accompanied by differences in oscillatory activity in mPFC during CS+ vs CS− presentation at retrieval adds to growing evidence of the involvement of this region in fear discrimination [27][28][29][30][31][32][33][34][35][36] . Although we found quantitative differences in theta and gamma power between CS+ and CS− presentation when activity was averaged over the entire frequency band and cue duration (see below), no qualitative differences were apparent when activity was examined throughout each frequency band or cue www.nature.com/scientificreports www.nature.com/scientificreports/ duration.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…Our finding of fear discrimination in males accompanied by differences in oscillatory activity in mPFC during CS+ vs CS− presentation at retrieval adds to growing evidence of the involvement of this region in fear discrimination [27][28][29][30][31][32][33][34][35][36] . Although we found quantitative differences in theta and gamma power between CS+ and CS− presentation when activity was averaged over the entire frequency band and cue duration (see below), no qualitative differences were apparent when activity was examined throughout each frequency band or cue www.nature.com/scientificreports www.nature.com/scientificreports/ duration.…”
Section: Discussionsupporting
confidence: 70%
“…We found IL gamma activation in response to the CS+ during retrieval, in keeping with other evidence indicating that this area is involved in fear discrimination 29,36 . Gamma oscillations mediate the functional connectivity between mPFC and primary auditory cortex that underpins successful auditory fear discrimination 35 , highlighting their importance for mediating communication within the neural circuitry underlying fear discrimination. Interestingly, we found that fear generalization in females was associated with a lack of gamma activation in IL at retrieval.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, the increase in gamma power observed during escape might reflect an increased emotional level compared to freezing. Indeed, previous studies both in humans and animals have shown that gamma oscillations are enhanced during emotional situations (reviewed in Headley and Paré, 2013;Stujenske et al, 2014;Concina et al, 2018).…”
Section: Freezing and Escape Differentially Modulate Brain Oscillatormentioning
confidence: 99%